ICF and SEN: a National project for identification toward quality of life model - Damiani, Paola; D'Anna, Cristiana; Gomez Paloma, Filippo (Education Sciences & Society - Open Access, 2019)
The school represents a privileged context for observing individual and social conditions, and for early interventions, according to an ecological and capability perspective. The Quality of Life model and the ICF model are valid references for the development of customized projects in this direction. Our study starts from the assumption that it’s necessary to work according to a model that meets a logic of possible defined relations among the areas in the anthropological paradigm of the ICF. Particularly it’s necessary to take advantage of the aims of Physical Education, a discipline that allows people to show themselves completely and to dialogue with the environment through the body. This research project has as its objective the validation of tools for the identification of Special Educational Needs through observation and evaluation of psycho-affective students’ indicators (Personal Factors of ICF and some essential factors of quality of life) during the lessons of Physical Education. Although the research data have not been collected yet to make an analysis, it’s useful the promotion of this project to realize a scientific model for the identification of SEN in the framework of the ICF, evaluating Physical Education that is often underestimated as interpretative key of students’ behaviors and educational failures.